Sucrose esters production in a solvent-free reaction system by transesterification of sucrose and fatty acid methyl esters (2018)
Abstract: This work studied the production of sucrose esters through the solvent-free transesterification of sucrose and methyl palmitate. Fundamentals of the process were studied to perform a conceptual design involving development of analytical techniques, measurement of physicochemical properties, phase equilibria, reaction kinetics, and process modeling. Analytic methods for the identification and quantification of reaction compound by HPLC were developed, and the main physical properties of the product (melting point, enthalpy of fusion, heat capacity, density, viscosity, among others) were either estimated or measured. The preliminary study of the reaction system allowed to prove that the use of emulsifiers as contact agents is effective to obtain similar reaction productivities to those obtained using the traditional solvent process. In addition, the main operational variables in the reaction system were studied (i.e. temperature, catalyst concentration, reactants ratio and emulsifier concentration) and later incorporated in a suitable kinetic model. Sucrose solubility in FAME was evaluated at the reaction conditions, and it was found that there is a synergic effect of sucrose esters in sucrose solubility. The solubility was adjusted to a phase equilibrium model, obtaining the corresponding binary interaction parameters, and this was incorporated within the kinetic model. Later, a brief experimental study of the separation system allowed to obtain an equivalent product compared with the commercial sucroesters. Based upon the physicochemical properties, the solid-liquid equilibria, the kinetic model, and the assessment of the separation operations, a conceptual process design for a portfolio of sucrose esters was proposed. From the preliminary economic analysis of the process it was found that the solvent-free process is potentially profitable and can compete with the traditional solvent process.